Identification and Management of Atherosclerotic Cardiovascular Disease Risk in South Asian Populations in the U.S - Agarwala, Anandita; Satish, Priyanka; Al Rifai, Mahmoud; Mehta, Anurag; Cainzos-Achirica, Miguel; Shah, Nilay S.; Kanaya, Alka M.; Sharma, Garima V.; Dixon, Dave L.; Blumenthal, Roger S.; Natarajan, Pradeep; Nasir, Khurram; et al. (JACC. Advances (Online), 2023)
South Asians (SAs, individuals with ancestry from Bangladesh, Bhutan, India, Maldives, Nepal, Pakistan, and Sri Lanka) are among the fastest growing ethnic subgroups in the United States. SAs typically experience a high prevalence of diabetes, abdominal obesity, and hypertension, among other cardiovascular disease risk factors, which are often under recognized and undermanaged. The excess coronary heart disease risk in this growing population must be critically assessed and managed with culturally appropriate preventive services. Accordingly, this scientific document prepared by a multidisciplinary group of clinicians and investigators in cardiology, internal medicine, pharmacy, and SA-centric researchers describes key characteristics of traditional and nontraditional cardiovascular disease risk factors, compares and contrasts available risk assessment tools, discusses the role of blood-based biomarkers and coronary artery calcium to enhance risk assessment and prevention strategies, and provides evidenced-based approaches and interventions that may reduce coronary heart disease disparities in this higher-risk population. [Display omitted] •South Asians experience a higher burden of CHD compared with adults of other racial/ethnic groups.•Culturally adapted assessment and management of traditional and nontraditional risk factors is essential.•Available population ASCVD risk assessment tools may be unreliable, particularly for those at borderline and intermediate risk; CAC testing may help refine risk and personalize care.•Evaluation of South Asian subpopulations will help characterize the contribution of social determinants, environmental influences, and genetic susceptibility on heterogenous cardiovascular disease burden.